Intervensi Health Coaching dalam Meningkatkan Pengetahuan dan Sikap Pencegahan Penularan Tuberkulosis - Evi Supriatun; Uswatun Insani (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of health coaching on knowledge and attitudes about the prevention of tuberculosis transmission in patients who are still undergoing routine tuberculosis treatment in Tegal Regency. The research design used was a quasi-experiment with pre and post-test with the control group. The results of the bivariate analysis showed that in the intervention group that had been given health coaching for 4 (four) sessions, it had a significant effect on the knowledge and attitudes of the respondents compared to the control group that was not given health coaching. This can be seen from the difference in values ​​before and after being given health coaching treatment in the intervention group. Also, the results of the bivariate analysis using the independent t-test showed a p-value of 0.000 <0.05. In conclusion, there is an effect of the implementation of health coaching on knowledge and attitudes about the prevention of transmission of tuberculosis in tuberculosis patients in Tegal Regency. Keywords: Health Coaching, Prevention of Tuberculosis Transmission, Knowledge, Attitude